1993
DOI: 10.12968/bjon.1993.2.14.705
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of professionals to drug abusers

Abstract: This article presents the preliminary findings of an interview study which examined the attitudes of 248 professionals working with intravenous drug abusers in Wcst/Central Scotland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 1 publication
1
26
0
1
Order By: Relevance
“…Substance abusers are regarded as a difficult patient group to deal with [18]. The abusers problems can often be extremely complicated and time demanding and often associated with verbal and/or physical abuse [18,26,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Substance abusers are regarded as a difficult patient group to deal with [18]. The abusers problems can often be extremely complicated and time demanding and often associated with verbal and/or physical abuse [18,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…The abusers problems can often be extremely complicated and time demanding and often associated with verbal and/or physical abuse [18,26,27]. This can lead to a fear of their security and irrational response as a consequence.…”
Section: Discussionmentioning
confidence: 99%
“…Those who are withdrawing will likely not be inclined and those who are intoxicated will often not be able to do so. Although chaotic drug users may not be wholly inconsiderate, the individuals with whom they interact (family members, professionals -including drug treatment providers -and the general public) often perceive them as dirty, undeserving, disagreeable and even frightening (Carroll, 1993;Murphy & Rosenbaum, 1999;Neale et al, 2008;Treloar & Holt, 2006). Despite this, research has indicated that individuals in recovery are concerned about how they present to other people (Biernacki, 1986;McIntosh & McKeganey, 2000, 2001a, 2001b and want to be cooperative and avoid conflict (Fischer, Neale, Bloor, & Jenkins, 2008;Matheson, 1998).…”
Section: Goffman Dramaturgy and Recoverymentioning
confidence: 99%
“…As service providers in Saskatoon were not consulted on this matter, it is unclear whether they are actually discriminatory towards IDUs or the participants simply perceive discrimination. However, stigma and discrimination among some service providers while dealing with IDUs is well documented in the literature (Carroll, 1993;Chan & Reidpath, 2007).…”
Section: Discrimination and Stigmatizationmentioning
confidence: 99%